Preclinical development of the quadrivalent meningococcal (ACYW) tetanus toxoid conjugate vaccine, MenQuadfi - Kensinger, Richard; Arunachalam, Arun B. (Glycoconjugate journal, 2022)
Bacterial capsular polysaccharide vaccines are generally poorly immunogenic in infants and older adults. The immunogenicity of capsular polysaccharide vaccines can be improved by conjugating them to immunogenic carrier proteins. One of the most recently licensed conjugate vaccines is the quadrivalent meningococcal vaccine with serogroups A, C, Y, and W conjugated to a tetanus toxoid protein carrier (MenACYW-TT; MenQuadfi, Sanofi Pasteur, Swiftwater, PA, USA). MenACYW-TT was developed to induce optimal immune responses against each of the meningococcal serogroups A, C, W, and Y, and across all age groups, especially infants and older adults (those aged ≥ 50 years). Here, we detail the early iterative vaccine development approach taken, whereby many different ‘small-scale’ conjugate vaccine candidates were prepared and examined for immunogenicity in a mouse model to identify the most immunogenic vaccine. Additional insights from phase I clinical studies informed further optimization of the vaccine candidates by tailoring their conjugation parameter attributes for the optimal immune response in humans. The parameters studied included: different carrier proteins [PR]; polysaccharide [PS] sizes; conjugation chemistries [linker vs. no-linker; lattice vs. neoglycoprotein; activation/derivatization levels]; conjugate size; PS:PR loading ratio; percent free PS; percent free PR; and O -acetylation content. The lead quadrivalent conjugate vaccine (polysaccharides of > 50 kDa size conjugated to TT at a high PS:PR ratio via reductive amination for serogroups C, W and Y, and carbonyldiimidazole/adipic acid dihydrazide linker chemistry for serogroup A) empirically identified from the extensive preclinical studies, was ultimately confirmed by the robust antibody responses observed in all age groups in the various clinical studies, including in the most challenging infant and older adult age groups, and subsequently led to the licensed formulation. Graphical abstract